الدفع بصغر السن أمام القضاء الجزائي الجزائري - محدة, فتحي (University of Eloued جامعة الوادي, 2022)
تعتبر دراسة الدفوع من المواضيع الهامة التي تسمح بتجسيد المحاكمة العادلة، واهتمام المشرع بفئة الأحداث من ناحية التشريع يجعل من الدراسات الفقهية المعالجة لموضوع الدفوع هي دراسات مكملة لها ومن أبرزها دراسة الدفع بصغر السن الذي يمكن أن نستخلص منه مجموعة من الدفوع التي تكون مؤثرة في مسار المتابعة الجزائية للحدث الجانح وهو توضحه الدراسة الحالية من خلال ما جاءت به المحكمة العليا من قرارات.The study of defenses is considered a crucial issue that enables fair trial realization. The legislator's interest in the juvenile category in terms of legislation; makes doctrinal studies dealing with the matter of defenses; complementary studies, and the most notable of which is the study of the defense of minor/underage children from which we can draw a set of defenses which are influential in the course of penal holding course of a juvenile delinquent, which is illustrated by the current study through the Supreme Court's decisions.
Defense of Underage Children before the Algerian Penal Judiciary
مقال
Keywords: الدفع ; حدث ; صغر ; السن ; جانح ; تدابير ; حماية; defense ؛ young ؛ small ؛ Age؛ delinquent؛procedures ؛ protection